Pendidikan Islam di Era Revolusi Industri 4.0 - Suharto (SALIHA: Jurnal Pendidikan & Agama Islam, 2019)
This paper is motivated by the condition of Islamic Education as an important subject in forming the noble values of students. Islam as a system of belief and belief greatly influences actualization in the context of education. The formulation of the problem posed is "What is the role of Islamic Education in facing the paradigm shift of the Industrial Revolution 4.0?" The expected objectives of this study will be to obtain a description of the roles that Islamic Education must meet in facing the changing industrial era 4.0. The results of the study show that the role of Islamic Education is very crucial because in facing the changing times it is necessary to maintain the noble values of religion which become the life guidance for the generation in facing it. The conclusion is that every implementation and implementation of Islamic Education must be able to direct students to act based on morality as stated in the Qur'an and the Sunnah and the agreement of the ulamas so that in this case Islamic education is ready to respond to such rapid changes that have a tremendous impact on life.